Modelling effects of water stress on the productivity of irrigated wheat (Triticum Aestivum L.) in a semiarid condition of Northeastern Nigeria - Muhammad Mansur Haruna; Habibu Ismail; Mohammed Sani; Ali Umar Bashir (SINERGI, 2023)
Lake Chad region is currently experiencing trending issues. Climate change is among the major influencers of these issues that require inevitable consideration for a sustainable ecosystem. Various crop models have been developed and employed in various environmental conditions and management practices, which are cheaper and easier than field experiments. Therefore, crop models could be used to simulate various water management strategies and suggest suitable options. In this work, the FAO AquaCrop model has been evaluated to simulate deficit irrigation (DI) scenarios for wheat crops using data generated from a field experiment. The model simulated grain yield (GY), biomass yield (BMY), biomass production (BMP) and canopy cover (CC) adequately during its calibration and validation. However, its performance in simulating water productivity (WP) and actual crop evapotranspiration (ETa) was low with average r2, NRMSE, model efficiency (EF) and Willmot Index of agreement (d) of 0.58, 11.0 %, -1.40 and 0.69 respectively. The study of DI scenarios using the model revealed that the application of DI throughout the growth stages of the crop could significantly affect GY and WP. The highest GY and WP of 5.3 t/ha and 1.50 kg/m3 were respectively obtained at the application of full irrigation (T100). Increasing DI beyond 20 % depressed both GY and WP significantly. However, increasing the irrigation interval from seven to ten days did not affect GY, thereby improving WP from 1.28 kg/m3 to 1.38 kg/m3. Therefore, applying an 80 % irrigation requirement throughout the wheat growing season at 10-day intervals could save 25 % of irrigation water, a valuable strategy to improve irrigation water use without significant yield reduction. Furthermore, irrigation-related scientists and managers can use the validated model to decide the current and future irrigation water management for similar wheat varieties in similar environmental conditions.